2015
DOI: 10.1111/1759-7714.12246
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of 14‐3‐3 σ, an early event of malignant transformation of respiratory epithelium, also facilitates progression of squamous cell lung cancer

Abstract: BackgroundIt has been shown that 14-3-3 σ serves as a tumor suppressor gene, and is downregulated in various tumor tissues. However, the role of 14-3-3 σ during the initiation and progression of lung squamous cell carcinoma (SqCC) is not well understood.MethodsThe expression status of 14-3-3 σ in archival tissue samples from 40 lung SqCC patients (36 with normal bronchia, 19 squamous metaplasia, and 17 dysplasia/carcinoma in situ, in their tissue samples) was examined by immunohistochemical analysis. The proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…However, previous studies have reported that in some other types of cancer, 14-3-3ζ may serve as a pro-tumor molecule ( 6 , 7 , 15 , 16 ). Thus, in our first step, we verified the role of YWHAZ in three typical cancers that have been commonly reported before, breast, lung and prostate cancer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, previous studies have reported that in some other types of cancer, 14-3-3ζ may serve as a pro-tumor molecule ( 6 , 7 , 15 , 16 ). Thus, in our first step, we verified the role of YWHAZ in three typical cancers that have been commonly reported before, breast, lung and prostate cancer.…”
Section: Discussionmentioning
confidence: 98%
“…The different binding ability may contribute to the contrasting role of different isoforms in a certain cancer type. As an instance, 14-3-3ζ promoted tumor invasion, while 14-3-3σ serves as a tumor-suppressor gene in non-small cell lung cancer ( 16 , 25 ). In addition, the expression level of 14-3-3 isoforms in tissue may be different ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that TJP1 might be a useful prognostic predictor of NSCLC [ 48 , 49 ]. YWHAE , a gene encoding 14-3-3 protein, was found to involve in carcinogenesis and progression of SCC [ 50 ]. Taken together, both our findings and previous reports suggested the critical roles of three miRNAs (miR-203, miR-205 and miR-375) in regulating Hippo signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of 14-3-3σ expression has been observed in several types of human cancers, including lung cancer, breast cancer and prostate cancer (12). Expression of 14-3-3σ is significantly downregulated in cancerous lung tissues and is associated with the differentiation grade and prognosis of the patient, whereas increased 14-3-3σ expression significantly suppresses the proliferation of lung squamous cell carcinoma cells (13). 14-3-3γ is frequently upregulated in lung cancer, accompanied by loss of functional p53, which suggests that the oncogenic activities of 14-3-3γ act synergistically with the loss of p53 to promote lung tumorigenesis (14).…”
Section: Introductionmentioning
confidence: 99%